Simple, Rapid Mycobacterium ulcerans Disease Diagnosis from Clinical Samples by Fluorescence of Mycolactone on Thin Layer Chromatography. - Anita Wadagni; Michael Frimpong; Delphin Mavinga Phanzu; Anthony Ablordey; Emmanuel Kacou; Mirabelle Gbedevi; Estelle Marion; Yalan Xing; Vaddela Sudheer Babu; Richard Odame Phillips; Mark Wansbrough-Jones; Yoshito Kishi; et al. (Public Library of Science (PLoS), 2015)
INTRODUCTION:Mycobacterium ulcerans infection, known as Buruli ulcer, is a disease of the skin and subcutaneous tissues which is an important but neglected tropical disease with its major impact in rural parts of West and Central Africa where facilities for diagnosis and management are poorly developed. We evaluated fluorescent thin layer chromatography (f-TLC) for detection of mycolactone in the laboratory using samples from patients with Buruli ulcer and patients with similar lesions that gave a negative result on PCR for the IS2404 repeat sequence of M. ulcerans. METHODOLOGY/PRINCIPAL FINDINGS:Mycolactone and DNA extracts from fine needle aspiration (FNA), swabs and biopsy specimen were used to determine the sensitivity and specificity of f-TLC when compared with PCR for the IS2404. For 71 IS2404 PCR positive and 28 PCR negative samples the sensitivity was 73.2% and specificity of 85.7% for f-TLC. The sensitivity was similar for swabs (73%), FNAs (75%) and biopsies (70%). CONCLUSIONS:We have shown that mycolactone can be detected from M. ulcerans infected skin tissue by f-TLC technique. The technique is simple, easy to perform and read with minimal costs. In this study it was undertaken by a member of the group from each endemic country. It is a potentially implementable tool at the district level after evaluation in larger field studies.